Racism in Sports: The English Football League as a Case Study - TOUAHAR, Halima; ZEGHDI, Zohra (University of Eloued جامعة الوادي, 2024)
This dissertation addresses the topic of racism in sports which is an important issue that the majority of people interested in following. This work focuses on football, the sport that attracts a large number of fans. The research sheds light on the roots of racism in the history of sports, with a focus on its spreading to the English Premier League. This dissertation aims to define racism within the English football league, examining its emergence and evolution over time. The study seeks to provide a detailed understanding of some pervasive issues including the players’ experiences and the surrounding responses. Besides providing a thorough examination of the prevalence and the impact of racism within the English football league, this dissertation offers an understanding of its manifestation and persistence in the sport. This research contributes to the ongoing dialogue on the complexities and the persistent existence of racial discrimination in football. Using the qualitative approach, the study employs a case study method by analysing incidents and cases of racial discrimination due to different reasons that make the Black players under pressure of various forms of discrimination in stadiums. It also evaluates the surrounding responses by the players’ teammates and the league. Moreover, by examining their responses through the data collected from press meetings, the players’ social media official pages, and their reported statements, the results highlight the contribution of the players in challenging discrimination and racism by raising awareness in addition to their activism. Besides the important role of sport in showing such sensitive social subjects like racism, the study concludes with reference to the major role of various organizations and anti-racist initiatives in combating this unethical phenomenon. The research advocates for implementing regulations that the people in the world and English societal scale should follow to eliminate such behaviors within stadiums and sports in general. يتناول هذا البحث موضوع العنصرية في الرياضة، وهو قضية ذات أهمية لغالبية الناس، وتركز بشكل خاص على كرة القدم، الرياضة التي تجذب عددًا كبيرًا من المشجعين من كلا الجنسين. تسلط الدراسة الضوء على جذور العنصرية في تاريخ الرياضة، ثم تخصص الدراسة للتركيز على انتشارها في الدوري الإنجليزي الممتاز. تستخدم الدراسة منهجية نوعية وتوظف أسلوب دراسة الحالة، حيث تحلل الحوادث والحالات التي تعرضت للتفرقة لأسباب مختلفة، مما يجعل اللاعبين تحت ضغط أشكال متنوعة من التمييز في الملاعب، بالإضافة إلى فحص ردود أفعالهم من خلال البيانات المجمعة من المؤتمرات الصحفية، والصفحات الرسمية للاعبين على وسائل التواصل الاجتماعي وتصريحاتهم المبلغ عنها. تبرز النتائج مساهمة اللاعبين في تحدي التمييز والعنصرية من خلال رفع الوعي ونشاطهم أيضًا. بالإضافة إلى الدور المهم للرياضة في إظهار مثل هذه المواضيع الاجتماعية الحساسة كالعنصرية. تقيم الدراسة ردود الفعل المحيطة من زملاء اللاعبين والدوري الانجليزي، لتختتم بإبراز الدور الحيوي للمنظمات والمبادرات المناهضة للعنصرية في مكافحة هذه الظاهرة غير الأخلاقية. علاوة على ذلك، تدعو الدراسة إلى تنفيذ القواعد التي يجب أن يتبعها الناس على الصعيد العالمي والمجتمع الإنجليزي للقضاء على هذه السلوكيات أو تحسينها داخل الملاعب والرياضة بشكل عام.
البشرة السوداء، العنصرية، الدوري الإنجليزي لكرة القدم، كرة القدم.
Keywords: Blackness; English Premier League; Football; Racism; البشرة السوداء، العنصرية، الدوري الإنجليزي لكرة القدم، كرة القدم.